Building a Culture of Peace in Everyday Life With Inter- and Transdisciplinary Perspectives - Roque-Hernández, Ramón Ventura (Frontiers in Education, 2022)
In this article, peace is emphasized as a vital condition for all aspects of our existence, as individuals, as a society, and in our planet. The importance of inter- and transdisciplinarity in promoting a culture of peace and peace education is presented. Some examples of initiatives aimed at cultivating a culture of peace from diverse areas of knowledge are also provided. The paper presents a current and interconnected viewpoint on peace study, as well as some ideas for combining peace with education in the everyday routine of teaching and research work, regardless of discipline.